A new species of Paraproto (Crustacea: Amphipoda) from southern New SouthWales, Australia - Guerra-García, José M.; Keable, Stephen J.; Ahyong, Shane T. (Zootaxa, 2020)
A new species of the caprellid genus Paraproto, P. murrayae n. sp. is described based on specimens collected from New South Wales, Australia. The new species was collected from brown algae in shallow water (16–19 m deep). Paraproto murrayae n. sp. is very similar to P. tasmaniensis Guerra-García & Takeuchi, 2004 but can be distinguished mainly by the following characteristics: (1) adults of P. murrayae are significantly smaller than P. tasmaniensis (5–6 mm and 10–11 mm respectively); (2) in larger males of P. tasmaniensis, gnathopod 2 is inserted on the anterior half of pereonite 2, rather than the posterior half as in P. murrayae; (3) the dactylus of the male gnathopod 2 is thickened medially in P. murrayae, but not thickened in P. tasmaniensis; (4) the setal formula of mandibular palp is 1-3-1 in P. murrayae versus 1-9-1 or 1-10-1 in P. tasmaniensis; (5) the lower lip is glabrous in P. murrayae but strongly setose in P. tasmaniensis; and (6) the anterolateral projections on pereonite 2 are lacking or vestigial in males of P. murrayae rather than distinct as in P. tasmaniensis. An illustrated key to the species of Paraproto is provided.